Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

f(x) = x^2 + 6x - 5
f(-1) =


Sagot :

Answer:

Step-by-step explanation:

x = -sqrt(5 f(-1) + 9) - 3, sqrt(5 f(-1) + 9) element R

Answer:

-10

Step-by-step explanation:

f(-1)=(-1)²+6(-1)-5

f(-1)=1-6-5

f(-1)=1-11

f(-1)=- -10